The median effective doses of propofol combined with two different doses of nalbuphine for adult patients during painless gastroscopy - Lili Tang; Chenxuan Ye; Nan Wang; Chen Chen; Sirui Chen; Shan Gao; Xuesheng Liu (Frontiers Media S.A., 2022)
Objective: Propofol is the most widely administered intravenous anesthetic to induce deep sedation for gastroscopy procedures. Coadministration of nalbuphine can provide analgesia and sedation to patients experiencing visceral pain, thereby decreasing the amount of propofol needed and reducing the risk of propofol-induced adverse events. We carried out this study to determine the median effective dose (ED50) of propofol in combination with different dosages of nalbuphine and the optimal dosage of nalbuphine during painless gastroscopy.Methods: We recruited sixty-five patients aged 18-60 years who underwent elective painless gastroscopy. A total of sixty-one patients were allocated randomly to the N1 group (nalbuphine 0.1 mg/kg) or N2 group (nalbuphine 0.15 mg/kg). Three minutes after administration of nalbuphine, patients received a preset dose of propofol at 2.0 mg/kg with a dose gradient of 0.2 mg/kg according to Dixon's "up-and-down" method. The primary outcome was the ED50 of propofol in combination with nalbuphine. Hemodynamic parameters, recovery time, pain score, and adverse events were recorded as secondary outcomes.Results: The ED50 of propofol in the N2 group was significantly lower than that observed in the N1 group (p < 0.01). Using probit analysis, the ED50 and ED95 of propofol were 1.632 mg/kg and 2.759 mg/kg in the N1 group and 1.111 mg/kg and 2.243 mg/kg in the N2 group, respectively. The incidence of hypotension in the N2 group was lower than that in the N1 group (p < 0.05), and the recovery time was shorter than that of the N1 group (p < 0.05).Conclusion: In adult patients, 0.15 mg/kg nalbuphine led to a significant reduction in the ED50 and ED95 of propofol during gastroscopy. This dose of nalbuphine also reduced the incidence of hypotension and shortened the recovery time. Therefore, nalbuphine (0.15 mg/kg) combined with propofol is a safe option for enhancing recovery after painless gastroscopy in adult patients.Clinical Trial Registration: [https://www.chictr.org.cn/edit.aspx?pid=126699&htm=4], identifier [ChiCTR2100053204].